Acute and Subchronic Inhalation Toxicity of n-Octane in Rats - Jae Hyuck Sung; Byung-Gil Choi; Hyeon Yeong Kim; Min-Won Baek; Hyun Youl Ryu; Yong Soon Kim; Young Kuk Choi; Il Je Yu; Kyung Seuk Song (Elsevier, 2010)
Objectives: We have investigated the toxic effects of the inhalation of subchronic and acute levels of n-octane. Methods: The rats were exposed to n-octane of 0, 2.34, 11.68 and 23.36 mg/L (n = 5 rats/group/gender) in an acute inhalation test (Organization for Economic Co-operation and Development (OECD) TG 403), or to 0, 0.93, 2.62 and 7.48 mg/L (n = 10 rats/group/gender) for a subchronic inhalation test (OECE TG 413), to establish a national chemical management system consistent with the Globally Harmonized Classification System (GHS). Results: Acutely-exposed rats became lethargic but recovered following discontinuation of inhalation. Other clinical symptoms such as change of body weight and autopsy finds were absent. The LC50 for the acute inhalation toxicity of n-octane was determined to exceed 23.36 mg/L and the GHS category was 'not grouping'. Subchronically-treated rats displayed no significant clinical and histopathological differences from untreated controls; also, target organs were affected hematologically, biochemically and pathologically. Therefore, the no observable adverse effect level was indicated as exceeding 7.48 mg/L and the GHS category was 'not grouping' for the specific target organ toxicity upon repeated exposure. Conclusion: However, n-octane exposure should be controlled to be below the American Conference of Industrial Hygienists recommendation (300 ppm) to prevent inhalation-related adverse health effects of workers.